Identification of a lipid metabolism-related gene for cancer immunotherapy - Jiang, Xin; Du, Wenqi; Shi, Ce; Kang, Mengjie; Song, Qiuya; Zhang, Lansheng; Pei, Dongsheng (Frontiers in Pharmacology, 2023)
Background: Tumors frequently evade immune surveillance through multiple pathways to escape T cell recognition and destruction. Previous studies indicated that lipid metabolism alteration could affect the anti-tumor immunity of cancer cells. Nonetheless, the studies that investigated lipid metabolism-related gene for cancer immunotherapy are still few. Materials and methods: By mining the TCGA database, we screened out carnitine palmitoyltransferase-2 (CPT2), a key enzyme in the fatty acid β-oxidation (FAO) process associated with anti-tumor immunity. We then analyzed the gene expression and clinicopathological features of CPT2 using open-source platforms and databases. Molecular proteins interacting with CPT2 were also identified using web interaction tools. Subsequently, the relationship between CPT2 and survival was analyzed in cancer patients. Results: Our study revealed that CPT2 played a vital role in tumor microenvironment and immune response signaling pathways. We have also demonstrated that increased CPT2 gene expression could enhance the level of tumor immune cell infiltration. Furthermore, high CPT2 expression positively related with overall survival associated with immunotherapy. CPT2 expression was also associated with the prognosis of human cancers, suggesting that CPT2 may be a potential biomarker for predicting the efficacy of cancer immunotherapy. Conclusion: To the best of our knowledge, the relationship between CPT2 and tumor immune microenvironment was first proposed in this study. Therefore, further studies on CPT2 may provide new insights into the development of effective cancer immunotherapy.